Meningkatkan Kemampuan Guru TK Dalam Menyusun RPPH Melalui Kegiatan Akademik dan Pendampingan - Santoso, Adi (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this research is that teachers can apply the Daily Learning Implementation Plan (RPPH) so that the 2013 curriculum targets can be realized properly. The research was carried out in the fostered kindergarten of Langkat district, Binjai district and was attended by 12 teachers. This school action research was carried out in two cycles. The analysis used is a quantitative descriptive technique. The results obtained from cycle one, namely the session of providing material and training sessions for the preparation of plans were sufficient as many as 12 people or 100%, and the ability in each aspect of the RPPH obtained one aspect (14%) got a good score and six components (86%) got a sufficient score. The results obtained from cycle II, namely the third session of deepening the material and the fourth session of giving assignments and evaluations showed that the participants who achieved good results were 12 people or 100%, and the ability in each aspect of the RPPH obtained 5 aspects (71%) got good scores and 2 aspect (29%) got enough score. From the results of the study, it was concluded that through academic supervision and assistance carried out by TK/PAUD supervisors, it was possible to improve the ability of teachers and kindergarten principals at the fostered kindergartens of Langkat district, Binjai district in preparing the Daily Learning Implementation Plan. Keywords: academic; accompaniment; Daily Learning Implementation Plan Abstrak: Tujuan penelitian ini agar guru dapat mengaplikasikan Rencana Pelaksanaan Pembelajaran Harian (RPPH) sehingga sasaran kurikulum 2013 dapat terealisasikan dengan baik. Penelitian dilaksanakan di TK binaan kabupaten Langkat kecamatan Binjai dan diikuti sebanyak 12 guru. Penelitian tindakan sekolah ini dilaksanakan dalam dua siklus. Analisis yang digunakan adalah teknik deskriptif kuantitatif. Hasil yang diperoleh dari siklus satu yaitu sesi pemberian materi dan sesi latihan penyusunan rencana cukup sebanyak 12 orang atau 100%, dan kemampuan dalam setiap aspek RPPH diperoleh satu aspek (14%) mendapat nilai Baik dan enam komponen (86%) mendapat nilai cukup. Hasil yang diperoleh dari siklus II yaitu sesi ketiga pendalaman materi dan sesi keempat pemberian tugas dan evaluasi menunjukkan bahwa peserta yang mencapai hasil baik sebanyak 12 orang atau 100%, dan kemampuan dalam setiap aspek RPPH diperoleh 5 aspek (71%) mendapat nilai Baik dan 2 aspek (29%) mendapat nilai cukup. Dari hasil Penelitian disimpulkan bahwa melalui supervisi akademik dan pendampingan yang dilakukan oleh Pengawas TK/PAUD dapat meningkatkan kemampuan guru dan kepala TK pada TK binaan kabupaten Langkat kecamatan Binjai dalam menyusun Rencana Pelaksanaan Pembelajaran Harian Kata Kunci: akademik; pendampingan; RPPH